2003
DOI: 10.1080/713743711
|View full text |Cite
|
Sign up to set email alerts
|

DC Electrical properties of graphytized carbon-black filled rubbers

Abstract: The dc electrical behavior of graphytized carbon-blacks filled rubbers was investigated in the temperature range 25 C to 125 C. The volume fraction of the fillers varied from 30% to 60%. The observed conductivity increases with increasing filler contents. At a temperature higher than 25 C for 60% filler concentration the behavior is ohmic, where at lower concentration two well defined regions were observed to indicate two types of conduction mechanism. The activation energy for conduction process increases fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…To study the electrical properties of the nanocomposites, an Everbeing EB-6 analytical probe station (Hsinchu, Taiwan) was used to measure the sheet resistances of the prospered specimens by using the four-point probe technique with a 2 mm pin interval. The studied nanocomposites with low hybrid filler concentrations (0.4 wt %) are expected to have the electrical conductivity near or below the percolation threshold of MWCNT/GNP/epoxy composites and the quantum tunneling effect is significant in the electrical conductivity [9,22,23,24,25]. The reason is that, according to the authors’ previous experimental results, under the same filler/matrix materials, filler concentrations, and specimen preparation conditions, the values of the percolation thresholds for the MWCNT/epoxy and GNP/epoxy composites are 3.5 and 0.9 wt %, respectively.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…To study the electrical properties of the nanocomposites, an Everbeing EB-6 analytical probe station (Hsinchu, Taiwan) was used to measure the sheet resistances of the prospered specimens by using the four-point probe technique with a 2 mm pin interval. The studied nanocomposites with low hybrid filler concentrations (0.4 wt %) are expected to have the electrical conductivity near or below the percolation threshold of MWCNT/GNP/epoxy composites and the quantum tunneling effect is significant in the electrical conductivity [9,22,23,24,25]. The reason is that, according to the authors’ previous experimental results, under the same filler/matrix materials, filler concentrations, and specimen preparation conditions, the values of the percolation thresholds for the MWCNT/epoxy and GNP/epoxy composites are 3.5 and 0.9 wt %, respectively.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The physical foaming is based on phase change of a foaming agent from the liquid phase to gas phase upon sudden pressure change. Carbon dioxide supercritical fluid is the most widely used foaming agent in polymers due to many advantages including high stability and low-cost [136,138]. Also, carbon dioxide acts as a processing aid by reducing the viscosity and surface tension of polymer melt [137].…”
Section: Nanofiller Alignmentmentioning
confidence: 99%
“…Nonetheless, previous authors' work has presented experimental evidence against this belief; the authors have demonstrated that the operating voltage does play an important role in the creep response of FSRs [39]; this behavior can be explained from the fact that tunneling conduction is voltage-dependent [40], thus causing nonlinear phenomena in the nanocomposite resistance. It must be highlighted that the voltage-dependent characteristic of CPCs has been independently reported by different authors [41][42][43], but usually, a current-voltage (I-V) characterization of CPCs is missing, i.e., although CPC manufacturing and characterization are active research trends in materials science [1,2,7,8,25,[31][32][33][34][35], the authors seldom include an I-V test in their invest igations, with only a few exceptions reported [41][42][43], and some of them reaching up to 50 V [44,45]. Electromechanical modeling of CPCs brings together multiple theories from statistics and thermodynamics [46]; quantum tunneling has been also embraced [47], but the practical effects of the sourcing voltage on the sensors' performance have not been extensively studied up until now.…”
Section: Introductionmentioning
confidence: 99%